Oegugin Influencers and pop nationalism through government campaigns: Regulating foreign-nationals in the South Korean YouTube ecology - Lee, Jin; Abidin, Crystal (Wiley-Blackwell, 2022)
In South Korea, it has become a growing trend for foreign Influencers to promote Korean cultures, especially through genres like mukbang (livestreamed binge-eating), beauty vlogs (e.g. “A day in the life of”), reaction (e.g., K-pop and K-drama “reacts”). This is observed in popular cross-platform hashtag streams like “oegugin” [#외국인; “foreign-nationals”], and “oegugin-baneung” [#외국인반응; “foreigner reactions”]. While institutions frequently deploy Influencers as ambassadors, the popularity of oegugin Influencers—particularly those of White descent—is prominently observed in South Korea alongside the global popularity of K-culture. In response, this paper details the emergent interventions toward the development and regulation of the oegugin Influencer ecology, by reviewing the strategic choices of oegugin Influencers when they work with government ministries and companies, especially around nation branding campaigns and contents. Specifically, we consider how the discourse of nation branding and nationalism is being shaped, promoted, and advocated by oegugin Influencers in the form of popular culture, despite Korea's existing racial system, which can be contentious for its entanglements with online hate and xenophobia. Further, we focus on what we call “pop nationalism” as evidenced in the oegugin Influencers' nationalist contents, and discuss how racial boundaries are regulated in the (re)production and consumption of such contents.